Oceanographic Structure and Light Levels Drive Patterns of Sound Scattering Layers in a Low-Latitude Oceanic System - Boswell, Kevin M.; D’Elia, Marta; Johnston, Matthew W.; Mohan, John A.; Warren, Joseph D.; Wells, R. J. David; Sutton, Tracey T. (Frontiers in Marine Science, 2020)
Several factors have been found to structure the spatial and temporal patterns of deep scattering layers (DSLs) including temperature, oxygen, salinity, light, and physical oceanographic conditions. We examine the variance in acoustically detected DSLs in the northern Gulf of Mexico and investigate the importance of multiple biotic and abiotic factors including mesoscale oceanographic conditions (e.g., Loop Current-origin water (LCOW), frontal boundaries (FB), and common water (CW)) in structuring DSLs. Results indicate heterogeneity in the vertical position and acoustic backscatter of DSLs relative to oceanographic conditions and light intensity. LCOW regions displayed consistent decreases (by a factor of two and four) in acoustic backscatter in the upper 200 m relative to FB and CW, respectively. DSLs had considerably greater backscatter at night in comparison to the day (25X for FB, 17X for LCOW, and 12X for CW). The importance of biotic (primary productivity) and abiotic (sea surface temperature, salinity) factors varied across oceanographic conditions and depth intervals, suggesting that the patterns in distribution and behavior of the mesopelagic assemblage in the northern Gulf of Mexico are highly dynamic.